PROCESSO DE ESCOLARIZAÇÃO DOS ALUNOS PÚBLICO-ALVO DA EDUCAÇÃO ESPECIAL NO BRASIL E NA ITÁLIA: UM ESTUDO COMPARADO - Breciane, Karolini Galimberti Pattuzzo (2020)
This study aims to map the materialization of public policies for Special Education, from a comparative perspective, in the municipalities of Cariacica/ES, Serra/ES and Sassari/Sardinia. We defend the thesis that the prescribed educational policy aimed at